Knowledge Level about Diabetes Mellitus of the population of Paso Ancho, San José Costa Rica, 2019. - Blanco, Aurelia (2021)
The research seeks to know the percentage of people who present an increased risk, as well as the level of knowledge of Type 2 Diabetes Mellitus of the population of Paso Ancho, San José, Costa Rica. Methodology: The American Diabetes Association (ADA) instrument of risk factors for the development of Diabetes Mellitus 2 was applied to 118 participants of the Health Fair. The Spanish version of the Diabetes Knowledge Questionnaire-24 (DKQ-24) was used to assess the level of knowledge about the disease in the study population. Finally, the Microsoft Excel and SPSS program were used to statistically process the data obtained in the surveys and instruments. Results: The average BMI was 27.9 Kg / m2. Only three women indicate having had gestational diabetes during their pregnancy period. 58% of the participants have at least one family member who has diabetes, 44% of them have high blood pressure (hypertension), of which 15 are men and 37 are women. Regards to physical activity, 53% of people indicate physical activity, of which 23 are men and 40 are women. Regarding the evaluation of knowledge about Diabetes Mellitus 2, it is observed that both sexes have a knowledge classified as not enough (90%).